An Enhancement of El Gamal Encryption Algorithm Applied in MD Message Controller through Mobile SMS - Dejacto, Jener Christian S. Morante, Rikka Alyssa V. 4 0 16; 5 (2017)
ABSTRACT This paper presents how to secure MD Message Controller, a mobile text messaging application, from malicious threats using El Gamal Cryptosystem. This paper shows issues that were discovered in the said algorithm. One of these problems is its inability to decrypt special characters without ASCII equivalent and this was solved by converting the plaintext to its Unicode equivalent. Another is its vulnerability to certain chosen-ciphertext attacks that made the existing El Gamal Algorithm not highly secured and lastly it consumes large memory than it should considering the ciphertext quadruples the number of characters of the plaintext. This research highlights that it is most significant that communication must be secured and protected against many kinds of threats.
Thesis: (BSCS major in Computer Science) - Pamantasan ng Lungsod ng Maynila 2017.
Keywords: 2 -- 0; 6; 20; 20; 2